2020
DOI: 10.1111/jvh.13310
|View full text |Cite
|
Sign up to set email alerts
|

Migratory flow and hepatitis delta infection in Italy: A new challenge at the beginning of the third millennium

Abstract: In Italy, HDV infection endemicity has greatly decreased overtime. Migratory flow may change this scenario as migrants often come from high HDV endemicity areas. Here, we studied characteristics of HDV infection in Italy, particularly addressed to the birth area of subjects. Chronic HBsAg carriers consecutively referring to 9 units in Italy prospectively enrolled for a six‐month period in 2019 were tested for anti‐HDV by ELISA. Multiple logistic regression analysis was performed to identify anti‐HDV positivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
1
30
1
Order By: Relevance
“…28 In Europe, the demise of HDV in domestic populations has been offset by new infections introduced by immigrants from areas where HDV remains endemic. 29 The relative proportion of HDV-infected migrants is increasing compared to HDV-infected native populations 30 ; migratory flows have interrupted the decline in infections, whose prevalence in HBsAg carriers stabilised in the last decade at 8-10% in Germany, Italy, Spain and France. 31 The pattern of decreasing domestic and increasing migrant HDV infections is being observed in all high-income countries.…”
Section: Hdv Infection In Europe and The Usmentioning
confidence: 99%
“…28 In Europe, the demise of HDV in domestic populations has been offset by new infections introduced by immigrants from areas where HDV remains endemic. 29 The relative proportion of HDV-infected migrants is increasing compared to HDV-infected native populations 30 ; migratory flows have interrupted the decline in infections, whose prevalence in HBsAg carriers stabilised in the last decade at 8-10% in Germany, Italy, Spain and France. 31 The pattern of decreasing domestic and increasing migrant HDV infections is being observed in all high-income countries.…”
Section: Hdv Infection In Europe and The Usmentioning
confidence: 99%
“…In Italy, several studies have shown a decreasing prevalence of Delta infection among chronic HBsAg carriers from 23.4% in 1987 8 to 8.3% in 1997 9 ; thereafter it remained stable around 10.0% during the first two decades of the third millennium 10–13 . In the last survey, 13 HDV prevalence among Italians further decreased to 6.4%; instead it was 26.4% among foreigners, outlining that migration flow counterbalances the residual cohort of long‐term native infections acquired during the 1970s and 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, another study conducted on 488 HBsAg-positive subjects [ 37 ] including 107 immigrants, found no difference in the HDV prevalence between Italian and immigrant subjects (7% and 7.3%, respectively). Instead, more recently, evaluating HDV prevalence in 786 HBsAg-positive subjects in 9 liver units prospectively enrolled for a 6-month period in 2019, the anti-HDV overall prevalence was 9.9%, 6.4% in Italian natives and 26.4% in non-natives [ 38 ].…”
Section: Discussionmentioning
confidence: 99%